2017
DOI: 10.1002/jbmr.3137
|View full text |Cite|
|
Sign up to set email alerts
|

Muramyl Dipeptide, a Shared Structural Motif of Peptidoglycans, Is a Novel Inducer of Bone Formation through Induction of Runx2

Abstract: Peptidoglycan fragments released from gut microbiota can be delivered to the bone marrow and affect bone metabolism. We investigated the regulation of bone metabolism by muramyl dipeptide (MDP), which is a shared structural unit of peptidoglycans. Increased bone and mineral density by enhanced bone formation were observed in mice administered with MDP. Remarkably, pretreatment or posttreatment with MDP alleviated bone loss in RANKL-induced osteoporosis mouse models. MDP directly augmented osteoblast differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…The expression of TNFα and the osteoclastogenic factor RANKL in bone was reduced in GF compared to CONV-R WT mice but not in Nod1 −/− or Nod2 −/− mice indicating that the effect of the GM to increase TNFα and RANKL in bone and to reduce bone mass is dependent on both NOD1 and NOD2 signaling. It was recently demonstrated that muramyl dipeptide (MDP), known as a shared structural unit of peptidoglycans from both gram-positive and gram-negative bacteria and a ligand to NOD2, regulates bone mass indicating that the NOD2 signaling pathway is involved in GM effects on bone [ 32 ].…”
Section: Effects Of Gm On Bone Metabolismmentioning
confidence: 99%
“…The expression of TNFα and the osteoclastogenic factor RANKL in bone was reduced in GF compared to CONV-R WT mice but not in Nod1 −/− or Nod2 −/− mice indicating that the effect of the GM to increase TNFα and RANKL in bone and to reduce bone mass is dependent on both NOD1 and NOD2 signaling. It was recently demonstrated that muramyl dipeptide (MDP), known as a shared structural unit of peptidoglycans from both gram-positive and gram-negative bacteria and a ligand to NOD2, regulates bone mass indicating that the NOD2 signaling pathway is involved in GM effects on bone [ 32 ].…”
Section: Effects Of Gm On Bone Metabolismmentioning
confidence: 99%
“…In addition, the GM also maintains bone homeostasis by regulating calcium absorption-related proteins and modulating tight junction proteins [ 11 , 16 , 17 ]. GM-derived lipopolysaccharide (LPS) and muramyl dipeptide (MDP) indirectly affect osteoclast proliferation and differentiation by inducing an inflammatory response [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are all upregulated when bone formation is increased. 16 Bone formation and bone resorption of subchondral bone directly affect subchondral bone microstructure.…”
mentioning
confidence: 99%